Templates, typologies and typifications: neoliberalism as keyword. Issue 2 (4th March 2019) - Rowe, Emma; Lubienski, Christopher; Skourdoumbis, Andrew; Gerrard, Jessica; Hursh, David
ABSTRACT: Neoliberalism as a concept, ideology, or theoretical lens has emerged in the last couple of decades as a monolithic presence in education research, and the social sciences more broadly. We bring two aims to this Special Issue: to critique the rigour of neoliberalism as a theoretical framework utilised within education research; and second, to explore and propose an alternative to neoliberalism as a critical frame of analysis. This paper will postulate three-waves of neoliberalism, specifically ordo-liberalism, radical liberalism, and post-neoliberalism. We challenge 'big-N' neoliberalism; conceptualisations of neoliberalism as homogenous and monolithic; and, demonstrate how neoliberalism interacts with particular milieus of time and space. In reflection of Williams but also Foucault's tracing of 'discursive formations', neoliberalism as a keyword points to a genealogy of power which requires further excavation. The notion of an assemblage, enabling mutations and contra configurations, may offer a way forward.